Predicting the hybridization state: a comparative study between conventional and innovative formulae - Arijit Das (Intelektual Pustaka Media Utama, 2020)
In previous published articles, formulae-based mnemonics by counting the total number of σ bonds with a lone pair of electrons (LP), a localized negative charge (LNC), or a localized lone pair of electrons (LLP) and subtracting one (01) from this total value (TSLP, TSLNC, or TSLLP) to predict the power of the hybridization state of simple molecules or ions and organic compounds, including heterocyclic compounds have been discussed. These are the innovative and time-efficient methods of enhancing student interest. Here, in this new article, the limitations of conventional formulae in comparison to the use of innovative formulae have been discussed along with the application of the hybridization state in different fields of chemical education. This article encourages students to solve multiple choice type questions (MCQs) at different competitive examinations in a time economic ground on the prediction of hybridization state of simple molecules or ions to know their normal and subnormal geometry and prediction of hybridization state of hetero atom in different heterocyclic compounds to know the planarity of the compounds, which is very essential factor for prediction of aromaticity of heterocyclic compounds. Educators can use this comparative study in their classroom lectures to make chemistry authentic and intriguing. Because the use of mnemonics in classroom lectures is an essential tool to become a distinguished educator.